Araguaia : entre palavras, roças e fuzis a pedagogia dos agentes pastorais no nordeste matogrossense, nos anos 1960/1970 - Santos, Paulo Cesar Moreira (2014)
In this dissertation we present a reflection on the case of Serra Nova Dourada, a small town located in the Middle Araguaia region, in the state of Mato Grosso, where several families in the early 1970s, were pressured to abandon their lands and to make way for new agricultural business that was being installed, in order to accomplish the project of the national and international capital linked to the military government. In this context I try to understand how concepts of education changed throughout the people’s struggle and resistance and which could have been the contribution of pedagogy used by pastoral agents for the permanence of rural families in their territory. The methodology covers the field of qualitative research within an investigative dialectical - historical approach and is based on survey and literature review, data collection in archives and interviews with various people involved in that historical process . To do this , I use the contributions and historical analysis of Casaldáliga ( 1971.1979 ) , Ianni (1981 ) , Picoli (2005 ) , Galletti (2000 ) , Paiva (2003 ) and other authors on the period , addressing some important aspects of the consolidation of the State of Mato Grosso and the politics of occupation of space by the military dictatorship. I also used the concepts of Paulo Freire on the process of awareness and quest for autonomy on the formation of individual and collective identity, and the search for recognition in the approach suggested by Honneth (2007 ) , as well as the contribution of Gramsci (1978 ) on the important articulation between theory and practice and the training of organic intellectuals . From the study it can be seen that the context of conflicts enabled the emergence of an alliance between peasant families threatened by expropriation of their lands and pastoral agents inserted in the middle of the Amazonian people . This integration has strengthened communities and class consciousness in the collision caused by the expansion of capital and, therefore , had as its main focus the issues of land, education and health. Seeking to break with the logic of exclusion and unequal balance of power that the scenario presented , the groups disregarded by the State resignify practices and common values , resize the space and choose the resistance from below.